THE FIELD SCHOOL OF HUMAN RESOURCES AS THE FORMING CHARACTER OF YOUTH ORGANIZATIONS IN MANGROVE MANAGEMENT ON THE COASTAL VILLAGE - Aditia, Dito; Suhendri, Hendrik; Gunawan, Cakti Indra; Yoga, Tirta; Baizuri, Akhmad; Munna, Kamila (Journal of Agricultural Socio-Economics (JASE), 2023)
The mangrove environment is one of the biological ecosystems in coastal regions with fluctuating plant organization, ecological nature and economic development. Nonetheless, the lack of human resources understanding of the functions of the mangrove is still undergoing. This article is written with the Systematic Review of literature and Training of the Institutional Capacity in Mangrove Ecosystem Management. The Field School of Human Resources as the Forming Character of Youth Organizations in Mangrove Management on the Coastal Village is an alternative strategy in order to achieve optimal and sustainable management and governance of mangrove forests. However, existing human resources in coastal areas must support optimal and sustainable mangrove management. Therefore, the seriousness of all stakeholders in realizing field schools for human resource development is a certainty.